International Environmental Agreements and Black Technology - Gilbert Kollenbach (Environmental and Resource Economics, 2022)
This paper analyzes the stability of international environmental agreements in a dynamic game when the generation of both renewables and fossil fuel based energy requires specialized capital stocks or technologies, respectively. Two contract types are considered. At an incomplete (a complete) contract, the coalition coordinates only (both) CO 2emissions (and renewable energy investments) of its members. In contrast to the results of Battaglini and Harstad (J Polit Econ 124:160–204, 2016) who endorse incomplete contracts to increase the coalition size, only small coalitions are stable regardless of whether the contract is complete or incomplete. This result also holds if black technology is temporary not completely used or transfers are considered.
Keywords: H87; Q54; Q55; 330; International environmental agreements; Black capacity; Complete contract; Incomplete contract